Computer aided learning in the community follow up module: a pilot study - Mohd Sidik, Sherina; S. A., Azlan Hamzah; Abdullah, Mohd Yunus; Md. Zain, Azhar; Ahmad, Zaiton (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
The need to deliver teaching material to undergraduates using the is compelling in view of the many advantages that the Internet provides. Report on the use of Computer Aided Learning (CAL) in teaching various major disciplines in medicine among. In view of this, the Faculty of Medicine and Health Sciences (FMHS), Universiti Putra Malaysia, embarked on a pilot study on the use of CAL for teaching of Year Four medical students undertaking the Community Follow-up Project (CFUP) to test the viability of CAL as a teaching method. Objectives: This paper describes our experience in the design and deployment of CAL as a complement to the traditional teaching methods of CFUP. We also present the findings of a survey on students’ opinion of the use of CAL in the CFUP. Methods: A website containing lecture notes and a discussion forum was set up to provide the CAL component. Students were asked to access the websites, download lecture notes and participate in a tutorial in the form of the discussion forum. A survey was conducted at the end of the CFUP to gauge students’ experience of computer use and their reaction to survey indicated that students were able to use the CFUP website and gained from the teaching material posted online. Discussion: A high percentage of our students possessed their own computers and all participants had access to the Internet. Students were able to access the website and participate in the discussion forum. Conclusion: The results demonstrate that it is viable to use CAL as teaching methods in the CFUP.